2011
DOI: 10.1186/1475-2840-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of mast cells in coronary artery endarterectomy of male patients with type 2 diabetes

Abstract: BackgroundType 2 diabetes is an important risk factor for the development of coronary artery disease (CAD). Focal or diffuse inflammation is often present in the vessels of patients with CAD. Mast cells are frequently present in the plaques as well as in the inflammatory infiltrates in the atherosclerotic vessel wall. In the study we wanted to examine whether there are differences in the morphology, number and distribution of mast cells and in their ability to modify the atherosclerotic process in coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is also known that osteopontin, a secretory product of mast cells and a potent inhibitor of ectopic calcification in intercellular valvular tissue, could prevent valvular tissue remodelling (Giachelli and Steitz, 2000;Steitz et al, 2002). Other studies suggested that diminished numerical density of impaired mast cells might be the reason for more extensive inflammatory and immunologic atherosclerotic changes in the vessel wall of coronary arteries in patients with coronary artery disease (Pleskovič et al, 2011), implicating that mast cells may play an important role in the protection of the integrity of endothelial cell layers and the vessel wall, probably via their paracrine activity, especially through the release of heparin (Pleskovič et al, 2011). The release of heparin as an anticoagulant substance, which leads to higher endogenous heparin levels and higher levels of IgE, may have the primary role in the protective function of vessel wall endothelial cells (Sinkiewicz, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that osteopontin, a secretory product of mast cells and a potent inhibitor of ectopic calcification in intercellular valvular tissue, could prevent valvular tissue remodelling (Giachelli and Steitz, 2000;Steitz et al, 2002). Other studies suggested that diminished numerical density of impaired mast cells might be the reason for more extensive inflammatory and immunologic atherosclerotic changes in the vessel wall of coronary arteries in patients with coronary artery disease (Pleskovič et al, 2011), implicating that mast cells may play an important role in the protection of the integrity of endothelial cell layers and the vessel wall, probably via their paracrine activity, especially through the release of heparin (Pleskovič et al, 2011). The release of heparin as an anticoagulant substance, which leads to higher endogenous heparin levels and higher levels of IgE, may have the primary role in the protective function of vessel wall endothelial cells (Sinkiewicz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…After deparaffinization, the sections were stained with HE, with toluidine blue solution (Pleskovič et al, 2011), and Movat pentachrome method to identify mast cells, or they were used for immunohistochemistry methods to identify T cells and macrophages. Histological analysis was performed by a trained pathologist blind to the treatment protocols.…”
Section: Staining Of Tissue Sections For Mast Cell Macrophage and T-c...mentioning
confidence: 99%
“…Numerous previous studies have focused on the role of mast cells (MCs) in AS and CHD. It has been found that MCs have involved in vascular plaque formation and inflammatory infiltration to atherosclerotic vessel walls through cell cytoplasmic vacuolization, extracellular extrusion of granules and nuclear sequestration [ 122 ]. MCs can secrete various mediators to activate other inflammatory cells (such as lymphocytes and foam cells) and affect the metabolism and circulation of HDL and LDL [ 123 , 124 ].…”
Section: Common Mechanisms Of Dvcsmentioning
confidence: 99%